Vitamin B(12) Derivatives as Activators of Soluble Guanylyl Cyclase - Proinsias, Keith ó (2012)
Various newly prepared and previously known vitamin B(12) derivatives have been studied as potential soluble guanylyl cyclase (sGC) activators. All compounds tested were found to activate the sGC enzyme, although to differing extents. The best results were obtained with the derivatives synthesized from c-lactone and possessing aliphatic amides in the c- and d-positions.